Briefing: Case studies for movement gauges to record vertical movements in structures to ±0·1 mm. Issue 3 (30th January 2019) - Thorniley-Walker, Robert; Bowers, Alice; Foley, Paul; Thew, Iain
Abstract : Extraordinary controversy continues to exist within the engineering profession over monitoring of movements and even over the underlying reason why useful and repeatable data are needed. Previous papers on this subject have shown that cracks only indicate the symptom of movement, but cannot reliably demonstrate the cause or even the form of movement. Monitoring of just the cracks often results in inadequate or inappropriate remedial works. Movement gauges can quickly and cheaply provide readings of relative vertical movements to 0·1 mm. Case studies illustrate advantages over the Building Research Establishment's precise levelling approach; how understanding of the characteristics of the ground movement helped forensic investigations of both a castle keep and a 1960s tower block; and how needless underpinning of a domestic property was avoided using vertical monitoring.